The contribution of eco bus technologies to environmental problem mitigation: a systematic review - Panuju, Achmad Yahya Teguh; Wahono, Endro Prasetyo; Sulistiyanti, Sri Ratna; Ibrahim, Gusri Akhyar (Institute of Advanced Engineering and Science, 2025)
Substituting diesel technology with eco-technologies in public buses is one of the prominent efforts being made to achieve a sustainable transportation system goal. Among these eco-technologies, commonly used ones include electric vehicles, natural gas fuel, hydrogen fuel, and bio-diesel fuel technology. However, the performance comparison between these technologies in reducing environmental impact at each location where they are implemented remains unanswered by previous studies. Research to measure the effectiveness of each of the eco-technologies in reducing environmental issues has been conducted extensively, employing various methods and metrics. This study conducted a systematic review of 94 articles that met the predefined inclusion criteria to obtain performance comparisons among these technologies. As a result, a general trend has been observed that eco-technologies have successfully achieved their intended goals with various success rates, although electric bus technology has advantages over other technologies based on the articles. However, its effectiveness relies on specific aspects to optimize its environmental performance. Therefore, the suitability of implementation in a region will depend on many factors. This article contributes to determining the extent to which eco-technologies are implemented in buses worldwide, serving as a consideration for decision-makers, and identifying research gaps in this topic.